Pengelolaan Media Sosial Instagram Kantor Wilayah Kementerian Hukum dan HAM Jawa Barat Dalam Memenuhi Informasi Publik - Arli Nursiwan; Rini Rinawati (Bandung Conference Series: Communication Management, 2022)
Abstract. Instagram social media management is a management strategy to fulfill a predetermined goal/target/function. Based on the embodiment of Law No. 14 of 2008 regarding public information disclosure (KIP) in facilitating relations between the government and its people, the Instagram account @kemenkumhamjabar has 14.9 thousand followers and the public satisfaction index for services (IKM) is 19.01 which is categorized as a very good index value. However, the lack of public interaction on the media account is an unfortunate concern, seeing from the success of achieving the number of followers and also the achievement of the satisfaction value that underlies the researchers wanting to know how to manage Instagram social media @kemenkumhamjabar in fulfilling public information. the subjects in the study focused on the division of Public Relations, Bureaucratic Reform, and Public Relations Information Technology which took part in managing the Instagram social media account @kemenkumhamjabar. The concept used in this research is the Circular Model of SoMe for Social communication which includes Share, Optimize, Manage, Engage to create an effective management that does not waste energy. The research uses the Qualitative Case Study method to explore data from one case in depth to reveal the reality behind the case. The results in this study at the Instagram share stage were chosen because of its popularity and millennials who are considered to gather a lot on Instagram social media. Optimize is done by optimizing the use of Instagram features even though they still look minimal, making captions, and hashtags have not been maximized. At the manage stage, it can be seen that there is no monitoring from the PR to observe the development of Instagram which makes Instagram @kemenkumhamjabar look monotonous and minimal interaction. And at the Engage stage, it is only done by collaborating with influencers but not doing research on the audience, namely followers of @kemenkumhamjabar. Abstrak. Pengelolaan media sosial instagram adalah suatu strategi pengelolaan untuk memenuhi suatu tujuan/target/fungsi yang sudah ditentukan. Berdasarkan perwujudan undang – undang nomor. 14 Tahun 2008 mengenai (KIP) keterbukaan informasi publik dalam memfasilitasi hubungan antara pemerintah dengan masyarakatnya, Akun instagram @kemenkumhamjabar memiliki followers 14,9 Ribu dan indeks kepuasan masyarakat kepada layanan (IKM) 19,01 yang dikategorikan sebagai nilai indeks yang sangat baik. akan tetapi minimnya interaksi publik di akun media tersebut menjadi perhatian yang disayangkan, melihat dari kesuksesan pencapaian jumlah followers dan juga peraihan nilai kepuasan yang mendasari peneliti ingin mengetahui bagaimana pengelolaan media sosial instagram @kemenkumhamjabar dalam memenuhi informasi publik. subjek dalam penelitian berfokus pada divisi Humas, Reformasi Birokrasi, dan Teknologi Informasi kehumasan yang ikut andil dalam mengelola akun media sosial instagram @kemenkumhamjabar. Konsep yang digunakan dalam penelitian ini Circular Model of SoMe for Social communication yang meliputi Share, Optimize, Manage, Engage untuk menciptakan pengelolaan yang efektif dan tidak menghabiskan tenaga. Penelitian menggunakan metode Kualitatif Studi Kasus untuk menggali data dari satu kasus secara mendalam untuk membuka realitas di balik kasus. Hasil dalam penelitian ini pada tahap Share instagram dipilih karena kepopuleranya serta kaum milenial yang dinilai banyak berkumpul di sosial media instagram. Optimize dilakukan dengan mengoptimalkan penggunaan fitur-fitur instagram walaupun masih terlihat minim, pembuatan caption, dan hastag belum dimaksimalkan. Pada tahap manage terlihat bahwa tidak adanya monitoring dari pihak humas untuk mengamati perkembangan instagram yang menjadikan instagram @kemenkumhamjabar terlihat monoton dan minim interaksi. Dan pada tahapan Engage hanya dilakukan dengan berkolaborasi dengan influencer tetapi tidak dilakukannya riset mengenai audiens yaitu followers @kemenkumhamjabar.